2001
DOI: 10.1002/per.386.abs
|View full text |Cite
|
Sign up to set email alerts
|

Personality, gender, and crying

Abstract: This study examined gender differences in crying as well as associations between basic personality traits and self-reported indices of crying. Forty-eight men and 56 women completed the Five-Factor Personality Inventory and the Adult Crying Inventory. Substantial gender differences were demonstrated in crying frequency and crying proneness, but not with respect to mood changes after crying. As predicted, women reported a higher frequency of crying and more proneness to cry both for negative and positive reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 4 publications
2
18
1
Order By: Relevance
“…The physical and mental reactions and changes also exhibit strong gender differences; for physical reactions, women report more crying than men in all samples ( χ 2 >14.1** for S1-S3), which is consistent with crying in general, where women have been shown to be higher in crying propensity and crying frequency [ 34 , 35 ]. There are also gender, musical expertise, and sample differences across the ratings of intensity and pleasure of the memorable experiences.…”
Section: Resultssupporting
confidence: 56%
“…The physical and mental reactions and changes also exhibit strong gender differences; for physical reactions, women report more crying than men in all samples ( χ 2 >14.1** for S1-S3), which is consistent with crying in general, where women have been shown to be higher in crying propensity and crying frequency [ 34 , 35 ]. There are also gender, musical expertise, and sample differences across the ratings of intensity and pleasure of the memorable experiences.…”
Section: Resultssupporting
confidence: 56%
“…Vingerhoets 2013 ). For example, previous research has shown that more neurotic individuals cry more often (De Fruyt 1997 ) and more easily (Peter et al 2001 ), while, for example, introverted and depressive individuals report more often the absence of mood benefits following crying (De Fruyt 1997 ; Rottenberg et al 2008b ). Kraemer and Hastrup ( 1988 ) tried to solve this issue of confounding individual differences by instructing participants to cry or to suppress their tears, but, as noted above, the adequacy of that solution is arguable because such a manipulation makes the situation rather artificial.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in crying frequency and crying proneness have been demonstrated, the latter ones still evident when controlling for personality differences (Peter et al 2001). Sex differences also extend to crying intensity, self-report of postcrying affect, and crying elicitors across interpersonal and stimulus situations (Lombardo et al 1983;Williams & Morris 1996).…”
Section: Children's Facial Expressions Of Pain In the Context Of Compmentioning
confidence: 93%